A review of long-term corneal preservation techniques: Relevance and renewed interests in the COVID-19 era - Sunita Chaurasia; Sujata Das; Aravind Roy (Indian Journal of Ophthalmology, 2020)
The growth of eye banking in India was showing positive trends until the nation was hit by unprecedented times as a result of the COVID-19 pandemic. The impact of this has led to a downward spiraling in eye banking activities globally. Several measures had to be implemented to tide over the crisis and strategies planned for future to prepare for the needs of corneal transplantation. While eye banks in India have been practicing short- term and intermediate storage preservation media, there is a definite need to evolve other methods of very long-term preservation. This review discusses various methods of long term corneal preservation, their relevance and applications in the present times. We reviewed relevant medical literature in English from PUBMED with the key words “Corneal preservation”, “Cryopreservation”, “Glycerol preservation”, Gamma Irradiation”, “Eye Banking” ,”COVID-19”.